Simultaneous Electrochemical Detection of Cu2+ and Zn2+ in Pig Farm Wastewater - Jia-Xin Du; Yang-Hao Ma; Said Nawab; Yang-Chun Yong (Sensors, 2024)
In recent years, the rapid development of pig farming has led to a large quantity of heavy metal-polluted wastewater. Thus, it was desirable to develop a simple heavy metal detection method for fast monitoring of the wastewater from the pig farms. Therefore, there was an urgent need to develop a simple method for rapidly detecting heavy metal ions in pig farm wastewater. Herein, a simple electrochemical method for simultaneous detection of Cu2+ and Zn2+ was developed and applied to pig farm wastewater. With a glassy carbon electrode and anodic stripping voltammetry, simultaneous detection of Cu2+ and Zn2+ in water was achieved without the need for complicated electrode modification. Furthermore, it was found that the addition of Cd2+ can enhance the response current of the electrode to Zn2+, which increased the signal by eight times. After systematic optimization, the limit of detection (LOD) of 9.3 μg/L for Cu2+ and 45.3 μg/L for Zn2+ was obtained. Finally, it was successfully applied for the quantification of Cu2+ and Zn2+ with high accuracy in pig farm wastewater. This work provided a new and simple solution for fast monitoring of the wastewater from pig farms and demonstrated the potential of electrochemical measurement for application in modern animal husbandry.